From the French Model to the European Space: review of the French Yearbook of Public Law - Ferraro, Francesca (Diritto Pubblico Europeo - Rassegna online, 2025)
The starting point of the French Yearbook of Public Law is an extensive dossier on climate change, used as a testing ground to question categories and remedies of public law in the Anthropocene. Around this thematic core develops an editorial project – curated by Philippe Cossalter and Jean-Bernard Auby – which assumes comparison as an ordering method and as an antidote to the autarchy of the French dogmatic tradition. Thus, an authentic laboratory that intertwines knowledge (legal and otherwise) and levels of government, connecting science, administration and political decision-making. Alongside the dossier, a comparative section reviews regulatory changes in the main European legal systems, highlighting convergences, gaps and hybridizations between models. The volume is closed by theoretical contributions on executive power and administrative procedure, presented as places for the redefinition of institutional balance. On the whole, the French Yearbook of Public Law is a solid platform for transnational discussion, capable of relaunching the transformative vocation of public law and of addressing the systemic urgencies of the present. Some editorial choices, however, allow a variety of tones, methods and objectives to emerge, which at times give prevalence to the idea of a collection of excellent contributions rather than that of a fully unitary design